Model-based processing scheme for quantitative 4-D cardiac MRI analysis. - Stalidis, G.
Presents an integrated model-based processing scheme for cardiac magnetic resonance imaging (MRI), embedded in an interactive computing environment suitable for quantitative cardiac analysis, which provides a set of functions for the extraction, modeling, and visualization of cardiac shape and deformation. The methods apply 4-D processing (three spatial and one temporal) to multiphase multislice MRI acquisitions and produce a continuous 4-D model of the myocardial surface deformation. The model is used to measure diagnostically useful parameters, such as wall motion, myocardial thickening, and myocardial mass measurements. The proposed model-based shape extraction method has the advantage of integrating local information into an overall representation and produces a robust description of cardiac cavities. A learning segmentation process that incorporates a generating-shrinking neural network is combined with a spatiotemporal parametric modeling method through functional basis decomposition. A multiscale approach is adopted, which uses at each step a coarse-scale model defined at the previous step in order to constrain the boundary detection. The main advantages of the proposed methods are efficiency, lack of uncertainty about convergence, and robustness to image artifacts.
Keywords: Boundary detection; Cardiac cavities; Cardiac magnetic resonance imaging; Coarse-scale model; Generating-shrinking neural network; Interactive computing environment; Learning segmentation process; Local information; Model-based processing scheme; Model-based shape extraction method; Myocardial surface deformation; Parametric modeling; Quantitative 4D cardiac MRI analysis; Quantitative cardiac analysis; Representation accuracy